Economic Analysis of Cattle Marketing in Gombe, Nigeria - Mohammed , Suleiman; Mohammed, Isiaka; Danjuma , Zahraddeen; Adamu, Ishaku (Asian Journal of Agriculture and Rural Development, 2013)
The study was conducted in 2010 to assess the profitability or otherwise of cattle marketing in Gombe, Gombe state, Nigeria. Data were collected using structured interview-schedule from 40 randomly selected cattle traders and were analyzed using budgeting technique. Results showed that the net income of small, medium and large size cattle was N6, 438.69, N11, 056.25 and N16, 474.64 per cattle respectively. Similarly, the respective values of gross return per each Naira invested were 1.18, 1.16 and 1.14 respectively while those of gross ratio were found to be 0.845, 0.846 and 0.876. On the other hand, average net income accrued to each trader per trading cycle were N19, 036.09, N 27, 215.39 and N 56, 837.50 for small, medium and large size categories of cattle, respectively. Thus, cattle marketing in the area were profitable and therefore recommended as an economic venture.